AORTOCAVAL PARAGANGLIOMA IN VON HIPPEL-LINDAU DISEASE: A RARE EXTRA-ADRENAL PRESENTATION WITH DISTINCT BIOCHEMICAL AND CLINICAL PROFILE - Mok, Meng Loong; Valayatham, Vijiya Mala (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pheochromocytomas and paragangliomas (PPGLs) are catecholamine-secreting tumors derived from chromaffin cells, with approximately 40% linked to germline mutations. One of the most common genetic associations is Von Hippel-Lindau (VHL) disease. VHL-related PPGLs typically arise in the adrenal glands, with only 10–20% occurring in extra-adrenal sites. Here we describe a patient who presented with VHL-associated aortocaval paraganglioma. CASE A 34-year-old female with poorly controlled hypertension on triple therapy presented with paroxysmal symptoms and worsening renal function since December 2023. She was admitted in May 2024 for hypertensive urgency and renal impairment. Ultrasonography and CT scan of the abdomen revealed a 6 cm retroperitoneal aortocaval mass. Biochemical tests confirmed elevated normetanephrine levels with normal metanephrine levels, and Ga-68 DOTATATE PET/CT imaging showed a somatostatin receptor-avid paraganglioma. Her family history was notable for a sibling with pheochromocytoma. She received adequate alpha-blockade, followed by successful surgical excision of the tumour. Histology confirmed a paraganglioma with low proliferative activity (Ki-67 <1%). Genetic testing revealed a VHL missense variant, confirming a diagnosis of VHL disease. Subsequent surveillance for other VHL-related manifestations revealed no additional tumours, and she is currently in remission for PPGL. Family screening identified five other individuals, including her young son, with the same genetic mutation; all are now undergoing regular follow-up. CONCLUSION VHL-associated PPGLs present at a younger age than sporadic cases and primarily secrete noradrenaline due to reduced PNMT expression, resulting from impaired hypoxic pathways caused by VHL loss. Patients often present with chronic hypertension and tachycardia. Functional imaging with 18F-DOPA PET/CT is preferred for its high sensitivity. These tumors have a low metastatic risk (5–8%) and rarely require systemic therapy. Given the high mutation penetrance of VHL disease (~90% by age 65), lifelong surveillance is essential. Early genetic and clinical monitoring enables timely detection in patients and at-risk relatives.